Spatiotemporal analysis of deforestation in the Chapare region of Bolivia using LANDSAT images. (28th July 2020) - Bagan, Hasi; Millington, Andrew; Takeuchi, Wataru; Yamagata, Yoshiki
Abstract: The purpose of this study is to quantify (a) spatiotemporal deforestation patterns, and (b) the relationships between changes in the main land‐cover types in the Chapare region of Bolivia. We applied subspace classification methods to LANDSAT data from 1986, 1999, and 2018 and used grid cells at scales of 150, 300, 600, and 900 m to measure deforestation trajectories. The 150 m grids provided better detail to determine deforestation trajectories than coarser‐scale grid cells. Differences in grid‐cell scale did not influence the statistical trends in land‐cover changes significantly. Changes in forest area were negatively correlated with changes in cropland ( r = −.44), grassland ( r = −.34), swamp grassland ( r = −.38), and regrowth ( r = −.32) areas. Correlations between forest losses in cropland, grassland, and regrowth change analyses were weaker between 1999 and 2018 compared to 1986 to 1999. Forest cover declined from 6, 635 km 2 (1986) to 3, 800 km 2 (2018), and the deforestation rate increased from an annual average of 1.36% between 1986 and 1999 to 2.0% between 1999 and 2018. The key proximate drivers of forest clearance rates and patterns were increasing population, agricultural expansion, and road building. While coca is an economically important crop in Chapare, its direct and indirect effects on deforestation could not be determined unambiguously. It is probable that the expansion of agriculture will lead to further deforestation and forest fragmentation and, along with decreases in forest cover, further changes will take place between non‐forest categories.